URGENSI DEWAN PENGAWAS SYARIAH (Studi Terhadap Implementasi Peran dan Fungsi Dewan Pengawas Syariah Pada Perbankan Syariah di Kota Metro) - Zulaikha, Siti (P3M STAIN Jurai Siwo Metro, 2013)
Sharia Supervisory Dewan (DPS) obliged to directly look at the implementation of an Islamic finance institutions in order not to deviate from the provisions of the Sharia Council has difatwakan by national (DSN) and the Council of Ulama Indonesia (MUI) which is domiciled in Jakarta. Sharia Supervisory Board should have the scientific knowledge in accordance with the criteria of a must-have. When the appointment was not based on DPS keilmuannya, then it could be ascertained, the function of supervision of DPS is not optimal, as a result of irregularities and the practice of Sharia is possible and happens all the time. It must be admitted, that Islamic banking is highly vulnerable to mistakes that are Shariah-compliant.This research aims to know and examine the existence of the Sharia Supervisory Board related to the function and its role in overseeing Sharia financial institutions in Metro City as well as knowing and analyzing the implementation of the role and function of the Sharia Supervisory Board in overseeing Sharia financial institutions in Metro City.Â Data collection preceded from activities identify and inventory data source a data source and data source material. After the required data are collected with a full finished, the next activity is the processing of data. The results of this research show that the role and function of the Sharia Supervisory Board is absolutely essential in order to maintain the purity of the teachings of Islam and she should deal in practice Sharia banking or financial institutions. Implementation of Syariah Supervisory Board at Islamic finance institutions in the City Metro, felt has not been optimal. Internally they are involved as a shareholder, not significantly impacting the externally linked to policies that are run by Islamic financial institutions management. Yet its optimal role of Sharia Supervisory Board allows violations of the Sharia in the Islamic finance business activities.Keywords : Implementation, the Board of Trustees of Sharia, Sharia Banking